If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2x + 7 + -2(2x + -3) = 6x + -3 + -1(x + -6) Reorder the terms: 8x + -2x + 7 + -2(-3 + 2x) = 6x + -3 + -1(x + -6) 8x + -2x + 7 + (-3 * -2 + 2x * -2) = 6x + -3 + -1(x + -6) 8x + -2x + 7 + (6 + -4x) = 6x + -3 + -1(x + -6) Reorder the terms: 7 + 6 + 8x + -2x + -4x = 6x + -3 + -1(x + -6) Combine like terms: 7 + 6 = 13 13 + 8x + -2x + -4x = 6x + -3 + -1(x + -6) Combine like terms: 8x + -2x = 6x 13 + 6x + -4x = 6x + -3 + -1(x + -6) Combine like terms: 6x + -4x = 2x 13 + 2x = 6x + -3 + -1(x + -6) Reorder the terms: 13 + 2x = 6x + -3 + -1(-6 + x) 13 + 2x = 6x + -3 + (-6 * -1 + x * -1) 13 + 2x = 6x + -3 + (6 + -1x) Reorder the terms: 13 + 2x = -3 + 6 + 6x + -1x Combine like terms: -3 + 6 = 3 13 + 2x = 3 + 6x + -1x Combine like terms: 6x + -1x = 5x 13 + 2x = 3 + 5x Solving 13 + 2x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 13 + 2x + -5x = 3 + 5x + -5x Combine like terms: 2x + -5x = -3x 13 + -3x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 13 + -3x = 3 + 0 13 + -3x = 3 Add '-13' to each side of the equation. 13 + -13 + -3x = 3 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = 3 + -13 -3x = 3 + -13 Combine like terms: 3 + -13 = -10 -3x = -10 Divide each side by '-3'. x = 3.333333333 Simplifying x = 3.333333333
| -44-7x=88x+16 | | -8+6+(-3)= | | 1x+3x=40 | | 188-6x=30x+16 | | -3(2x-5)+7=(3-x) | | 103-4x=4x+7 | | T=3m+3z | | -3(2x-5)7=(3-x) | | x+(x+3)=23 | | 3x-2=80 | | x/0.6=9.3 | | 6x+12-7=41 | | 6k-4=2k+8 | | -2+3y=12 | | 4(11x+2)-17=23x-2 | | 4x^2-16=8 | | 139144= | | 8x-(x+3)=11 | | 6(3f-10)=30 | | 80+y^2=0 | | (a-4)*(a+4)= | | 6x+12=-58-8x | | 2x-6=-x+15 | | 3x+9x+10=13 | | 5u(2u+3)-2u(u-7)= | | 2x+127=12x-13 | | 3c^2-3c=4c | | 9-7x=84-42x | | 2x-5x=10 | | 5x^2-55x+20=0 | | 10-7x=103-28x | | x^2-16=-13 |